Contemporary Clinical Management of the Cerebral Complications of Preeclampsia - Stefan C. Kane; Alicia Dennis; Fabricio da Silva Costa; Louise Kornman; Shaun Brennecke (Obstetrics and Gynecology International)
The neurological complications of preeclampsia and eclampsia are responsible for a major proportion of the morbidity and mortality arising from these conditions, for women and their infants alike. This paper outlines the evidence base for contemporary management principles pertaining to the neurological sequelae of preeclampsia, primarily from the maternal perspective, but with consideration of fetal and neonatal aspects as well. It concludes with a discussion regarding future directions in the management of this potentially lethal condition.